Improving Phonological Awareness in Parents of Children at Risk of Literacy Difficulties: A Preliminary Evaluation of the Boost Program - Boyes, Mark E.; Leitão, Suze; Claessen, Mary; Dzidic, Peta; Boyle, Gemma; Perry, Alison; Nayton, Mandy (Frontiers in Education, 2017)
Background Phonological awareness is an important skill underpinning the development of early literacy. Given the central role of parents in supporting the development of children’s early literacy skills, and that poor parental phonological awareness is associated with poorer child literacy outcomes, it is possible that improving parent phonological awareness may aid literacy development for at-risk children. This study is a preliminary evaluation of a program aiming to improve phonological awareness skills of parents in low socioeconomic status communities, and also provide these parents with strategies to support their child’s literacy development. Methods After completing the program, participants were asked if it had helped them learn about how to assist their child’s reading and spelling, whether they planned on using the resources provided, and if they would be likely to attend a future workshop building on the Boost program. Phonological awareness measures (rhyme, syllable, and phoneme level), and measures of overall confidence in performance on the phonological awareness tasks, were administered both before and after attending the program. Results Almost all parents indicated that the program helped with learning how to assist their child’s reading and spelling, that they would use the resources provided, and would likely attend a future workshop. Significant increases in pre- to post-program phonological awareness scores were obtained at the rhyme and phoneme level. Conclusion The program and associated resources appear acceptable to parents in communities with high rates of literacy problems and improved parents’ phonological awareness skills. However, findings are preliminary and further evaluation using more rigorous methodologies and testing whether improvements in parents’ phonological awareness translate into better literacy outcomes for children is needed.